Using E-Book Readers to Foster EFL Students’ Multi-Literacies (A Case Study at a Vocational High School in Ciamis) - Melinda Wulandari (Journal of English Education Program (JEEP), 2023)
This paper reports on the implementation of E-book Readers as a media to foster EFL students’ multi-literacies in one of vocational high school in Ciamis. This research is aimed at discovering how E-book Readers can foster EFL students’ multi-literacies, discovering kind of multi-literacy which will be indicated by students, and finding out students’ responses on E-book Readers. This research employed a case study with one class of the eleventh grade as research participant. This study also used observation, interview, and questionnaire to access the data. Those data from interview and classroom observation were analyzed by transcribing the data, while the questionnaires were analyzed by using percentage calculation. The findings of this research revealed the implementation of E-book Readers as a media in English learning process in the classroom. E-book Readers as a media to be applied in learning process can involve students in various kinds of literacy. Students can search their material and knowledge using E-book Readers. Students can also foster multi-literacies just only by using E-book Readers. The process of those learning activities enables students to be active in learning. The questionnaire results also revealed that most of students gave positive response on the use E-book Readers by the teacher in learning English. Some suggestions were presented for those who might benefit from this study. There is the advantage for the teacher who teaches English and also for the students who study English, E-book Readers can be helpful for them when they are used in teaching and learning process. Further researchers are suggested to search for more references about the media of E-book Readers. They are also suggested to carry out further research through E-book Readers media on the result of learning, in order to manifest national education goal.